African swine fever virus MGF505-4R facilitates cGAS degradation through TOLLIP-mediated selective autophagy and inhibits the formation of ISGF3 to evade innate immunity - Manman Yao; Pengfei Li; Xiangmin Li; Wentao Li; Ping Qian (Veterinary Research)
Abstract African swine fever virus (ASFV) causes acute and highly lethal disease in pigs. To counteract host defense systems and facilitate virus infection, many ASFV-encoded proteins have regulatory effects on the innate immune response. In this study, we constructed an MGF505-4R-deleted ASFV strain (ASFV-Δ4R) and found that, compared with the wild-type ASFV, ASFV-Δ4R infection significantly increased IFN-β production and elevated the mRNA levels of antiviral genes in porcine alveolar macrophages. Mechanistically, MGF505-4R interacts with cGAS and promotes its degradation by triggering Toll-interacting protein (TOLLIP)-mediated selective autophagy. Specifically, MGF505-4R enhanced the interaction between cGAS and TOLLIP, which subsequently led to increased degradation of cGAS. Additionally, MGF505-4R inhibited IFN-β-induced signal transmission by interacting with STAT1 and STAT2 and impeding their phosphorylation. This effect consequently prevented the formation of the ISGF3 heterotrimer and its subsequent translocation to the nucleus, leading to the downregulation of antiviral genes. As expected, compared with the ASFV-WT strain, ASFV-Δ4R infection increased phosphorylation of STAT1 and STAT2 and subsequent ISGF3 formation, leading to an elevated expression of antiviral gene ISGs. This discovery enhances the understanding of the immune regulation strategies evolved by ASFV and offers valuable perspectives for antiviral research targeting ASFV.